Impact of Air Pollution Fee Rates on Enterprises in the Czech Republic - Sidorov, Egor; Ritschelová, Iva (Univerzita Pardubice, 2008)
This article presents the partial results of the most extensive analysis ever made in the Czech Republic focusing among others at the impact of air pollution fee rates on enterprises. The authors consider the history as well as the current purposes of the environmental protection fees system in the Czech Republic. The conclusion is made that air pollution fees in the Czech Republic at the current level as well as the possible update being prepared are too low to positively stimulate enterprises to environmentally positive behaviour.
Keywords: air pollution fees; environmental policy; Enterprise; economic impact; Czech Republic